A Highly Efficient Non‐Fullerene Organic Solar Cell with a Fill Factor over 0.80 Enabled by a Fine‐Tuned Hole‐Transporting Layer. Issue 34 (10th July 2018) - Zheng, Zhong; Hu, Qin; Zhang, Shaoqing; Zhang, Dongyang; Wang, Jianqiu; Xie, Shenkun; Wang, Rong; Qin, Yunpeng; Li, Wanning; Hong, Ling; Liang, Ningning; Liu, Feng; et al.
Abstract: With rapid development for tens of years, organic solar cells (OSCs) have attracted much attention for their potential in practical applications. As an important photovoltaic parameter, the fill factor (FF) of OSCs stands for the effectiveness of charge generation and collection, which significantly depends on the properties of the interlayer and active layer. Here, a facile and effective strategy to improve the FF through hole‐transporting layer (HTL) modification is demonstrated. By mixing WO x nanoparticles with a poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) emulsion, the surface free energy of the HTL is improved and the morphology of the active layer is optimized. Benefiting from increased carrier lifetime, a device based on WO x :PEDOT:PSS HTL exhibits a boosted performance with an FF of 80.79% and power conversion efficiency of 14.57% PCE. The results are certified by the National Institute of Metrology (NIM), which, to date, are the highest values in this field with certification. This work offers a simple and viable option of HTL modification to realize highly efficient OSCs. Abstract : Highly efficient polymer solar cells are attained through a finely tuned hole‐transporting layer based on tungsten oxide:poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (WO x :PEDOT:PSS). This strategy enables power conversion efficiencies over 14.5% and fill factor over 80.7% to be achieved with a single‐junction device configuration.